Development and reliability testing of a tool to assess knowledge, attitude, and practice regarding physical restraint - Kavumpurath, Janisha; Devaraj, Navin Kumar; Mani, Kulanthayan KC; Ahmed, Fatma Refaat; Ibrahim, Noor Airini; Abdul Rashid, Aneesa (Pakistan Medical Association, Rawalpindi Islamabad Branch, 2022)
Objective: To develop a reliable and accurate measurement tool for assessing critical care nurses' knowledge, attitude, and practice in the area of physical restraint and create an instructional module on physical restraint for critical care nurses. Methodology: The technique for creating and validating the tools involved several steps: (a) creating a theoretical framework and conducting a literature review; (b) developing the instructional module and tool items; (c) determining validity, and (d) pilot testing. A knowledge questionnaire, an attitude scale, a self-reporting practice checklist, and an instructional module were among the tools we produced. We examined the tools through face validity and content validity. We pilot tested the tool on a total of 20 critical care nurses, dividing them into 10 subjects each: experimental and control. Results: The items were assessed on their clarity, easy comprehension, and whether they effectively captured the subject being assessed, and they incorporated the expert’s suggestions into the tool development. In the questionnaire, the content validity ratio (CVR) of the item must be greater than or equal to 0.99 to be considered. Cronbach’s alpha done for the knowledge (0769 vs 0.764), attitude (0.694 vs 0.828) and practice (0.766 vs 0.624) domains show that the items have an acceptable level of internal consistency in both study groups. Conclusions: The assessment tool developed was validated by experts in the field and tested for reliability. With a good reliability score, it may be used as a tool in the field of physical restraint.